2001
DOI: 10.1080/10473289.2001.10464326
|View full text |Cite
|
Sign up to set email alerts
|

Washing of Marine Coastal Sand in a Batch Reactor: Sorption and Desorption of BTEX

Abstract: This study addresses the issues related to decontamination of marine beach sand accidentally contaminated by petroleum products. Sorption and desorption of BTEX (i.e., benzene, toluene, ethylbenzene, and xylene) onto the sand from Uran Beach, located near the city of Mumbai, India, were studied, and isotherms were determined using the bottle point method to estimate sorption coefficients. Alternatively, QSARs (i.e., quantitative structure activity relationships) were developed and used to estimate the sorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Barry et al (2002) reported that the Langmuir model is applicable to cases in which sorption is limited to a finite capacity that is being represented [42]. Many studies on the sorption of various dissolved organic compounds onto the soil have reported that the Freundlich and linear models are more suitable than the Langmuir model [43][44][45]. This is because all models are similar to the linear model at low concentrations [46].…”
Section: Suitability Of Non-linear Equilibrium Modelsmentioning
confidence: 99%
“…Barry et al (2002) reported that the Langmuir model is applicable to cases in which sorption is limited to a finite capacity that is being represented [42]. Many studies on the sorption of various dissolved organic compounds onto the soil have reported that the Freundlich and linear models are more suitable than the Langmuir model [43][44][45]. This is because all models are similar to the linear model at low concentrations [46].…”
Section: Suitability Of Non-linear Equilibrium Modelsmentioning
confidence: 99%
“…Soil and sediment concentrations of benzene and the related compounds toluene, ethylbenzene, and the xylenes (BTEX) are routinely determined by U.S. EPA Method 5035/5030, which uses water (or methanol) extraction followed by purge-andtrap analysis. Several investigators have demonstrated that environmental aging of hydrophobic organics can reduce their bioavailability and their rates of desorption into water (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Studies on aromatic hydrocarbons have focused on multi-ring PAHs since their water solubilities are much lower than BTEX compounds (7,8,10,11).…”
Section: Introductionmentioning
confidence: 99%